Reliability of information available on popular websites about vaccination of pregnant women - Pereira, Carolina Guedes; Santos, Raquel Freire; Faria, Ana Paula Vieira; Silva, Thales Philipe Rodrigues da; Pena, Érica Dumont; Matozinhos, Fernanda Penido (Revista da Escola de Enfermagem da USP, 2021)
Objective: To analyze the reliability of information available on popular websites about vaccination of pregnant women according to the recommendations of the Brazilian Ministry of Health. Method: Descriptive and comparative study. For data collection, a checklist composed of information on recommended, contraindicated, and indicated vaccines in special situations during pregnancy, according to the Ministry of Health, was elaborated. Results: None of the analyzed websites presented all the recommended information. Contraindications, most common adverse events, simultaneous administration of vaccines, information on the DT vaccine, and recommended vaccines in special situations were presented by a minority of websites. Conclusion: Information available on websites about the vaccination of pregnant women is not always based on the recommendations and misinformation may interfere with the acceptance of this practice. The importance of the professionals of the multidisciplinary team as information mediators, particularly the nurse, is emphasized, as is the need for regulating the production and dissemination of information on the internet.